How to Increase Post-Thaw Semen Quality in Poor Freezing Stallions: Preliminary Results of the Promising Role of Seminal Plasma Added after Thawing - Šichtař, Jiří; Bubeníčková, Filipa; Sirohi, Jitka; Šimoník, Ondřej (Animals, 2019)
The aim of this study was to evaluate the effect of the addition of two types of seminal plasma (SP) after thawing on the functional characteristics of frozen-thawed (F-T) spermatozoa of poor freezing stallions during prolonged incubation periods. Seminal plasma from stallions with 35-40% (standard seminal plasma, (S-SP)) and 60-70% (above standard seminal plasma, (A-SP)) progressively motile spermatozoa after thawing was used. The motility, kinematic parameters (Computer Assisted Sperm Analysis), distribution of spermatozoa into subpopulations, integrity (carboxyfluorescein diacetate/propidium iodide staining), and functionality (hypo-osmotic swelling (HOS) test) of the spermatozoa plasma membrane were evaluated after thawing (T0) and after 30 min (T30) of incubation at 37 °C. There was no effect of SP addition on spermatozoa motility, but there was a significant positive effect on the kinematic parameters at T0 and T30. The addition of SP significantly increased the percentage of spermatozoa in the fast subpopulation at T0 as well as at T30. Plasma membrane integrity was not affected by the treatment, but functionality significantly decreased by 5% compared to the control group when samples were incubated for 30 min with A-SP. In conclusion, generally, the post-thaw addition of seminal plasma positively affected the post-thaw quality of semen from poor freezing stallions.
Keywords: cryopreservation; horse; semen; freezability